Aminomethylphosphonic acid has low chronic toxicity to Daphnia magna and Pimephales promelas. (17th April 2015) - Levine, Steven L.; von Mérey, Georg; Minderhout, Tui; Manson, Philip; Sutton, Peter
Abstract Aminomethylphosphonic acid (AMPA) is the simplest member of a class of compounds known as aminomethylenephosphonates and the only environmental metabolite measured in significant amounts during the degradation of the herbicide glyphosate in soil. However, there are additional sources of AMPA in the environment, originating from organic phosphonates which are used in water treatment to inhibit scale formation and corrosion. Like glyphosate, AMPA has low acute toxicity to aquatic animals, and the no‐observed–adverse effect concentration (NOAEC) obtained from a fish full–life cycle study for glyphosate was determined to be 26 mg/L. However, the chronic toxicity of AMPA to aquatic animals has not been evaluated before. The purpose of the present study was to assess the potential for chronic toxicity of AMPA to fathead minnow (Pimephales promelas) and Daphnia magna. Chronic toxicity to P. promelas was evaluated in a fish early–life stage study. The primary endpoints were larval survival, growth, and development. The NOAEC for P. promelas was determined to be 12 mg/L, the highest concentration tested. The chronic toxicity to D. magna was evaluated in a Daphnia reproduction test. The primary endpoints were survival, growth, and reproduction. The no‐observed‐effect concentration for D. magna was determined to be 15 mg/L. Conservatively predicted environmental surface water concentrations for AMPA from typical foliar agricultural application rates and values from surface water monitoring programs are 100 to 1000 times less than the NOAEC values from both studies. Consequently, there is a large and highly protective margin of safety between realistic environmental exposures to AMPA and chronic toxicity to aquatic vertebrates and invertebrates. Environ Toxicol Chem 2015;34:1382–1389. © 2015 The Authors. Published by Wiley Periodicals, Inc. on behalf of SETAC.